Effects of component proportions on multi-jet instant expansion of binary solutions under flash boiling conditions. (15th January 2022) - Zhou, Ze; Li, Yanfei; Zhang, Jingyu; Wang, Yu; Yan, Fuwu; Xu, Hongming
Highlights: Effects of component proportions on the instant expansion were revealed. Rp was not suitable to quantify the instant expansion for binary solutions. A new index ΔQ′ was proposed for binary solution spray. Abstract: Flash boiling injection can significantly promote spray atomization owing to rapid bubble growth and explosion. Nevertheless, the effects of component proportions on spray expansion of multi-component fuels still need more quantitative studies. In this work, a typical non-ideal binary solution (aqueous ethanol solution) was utilized as the injection fluid. The effects of ethanol proportion at varying injection temperatures and ambient pressures were tested in a constant volume vessel. Both increasing injection temperature and decreasing ambient pressure intensified the flashing instant expansion for all tested fluids. Instant expansion of pure water spray can be intensified by adding ethanol but adding ethanol into the aqueous ethanol solution induced an opposite behavior. Such phenomenon was caused by the combined effect of differences in heat capacity and proportions of evaporation components. Hence, superheat level was no longer a suitable index for evaluating the instant expansion between sprays with different component proportions. A new index ΔQ′ was proposed to quantify the expansion extent of binary solutions. A strong correlation was found between expansion extent and ΔQ′∙Pamb −0.75 over a wide condition range, indicating the superheated energy available for the first-vaporizable part of the solution is an important factor controlling the extent of instant expansion for binary solution spray.